2020
DOI: 10.1128/msystems.00070-20
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Study of Substrate-Specific Transport Mechanisms for Iron and Carbon in the Marine Copiotroph Alteromonas macleodii

Abstract: Iron is an essential micronutrient for all microbial growth in the marine environment, and in heterotrophic bacteria, iron is tightly linked to carbon metabolism due to its central role as a cofactor in enzymes of the respiratory chain. Here, we present the iron- and carbon-regulated transcriptomes of a representative marine copiotroph, Alteromonas macleodii ATCC 27126, and characterize its cellular transport mechanisms. ATCC 27126 has distinct metabolic responses to iron and carbon limitation and, accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…Alteromonas has been found to make significant contributions to iron metabolism ( 20 , 21 ) and play an important role in marine organic carbon and nitrogen cycling ( 22 ). In laboratory cocultures with cyanobacteria like Prochlorococcus , Synechococcus , and Trichodesmium ( 23 ), Alteromonas has demonstrated broad substrate preferences and can utilize dissolved organic carbon and particulate organic carbon supplied by photoautotrophs ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alteromonas has been found to make significant contributions to iron metabolism ( 20 , 21 ) and play an important role in marine organic carbon and nitrogen cycling ( 22 ). In laboratory cocultures with cyanobacteria like Prochlorococcus , Synechococcus , and Trichodesmium ( 23 ), Alteromonas has demonstrated broad substrate preferences and can utilize dissolved organic carbon and particulate organic carbon supplied by photoautotrophs ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, PepSY-like gene clusters have been shown to be repressed by Fur (the primary transcription regulator that responds to iron limitation) in Shewanella oneidensis and Caulobacter crescentus ( da Silva Neto et al, 2013 ; Wan et al, 2004 ). Moreover, in some cases, PepSY-like proteins may be actively involved in the extraction of siderophore-bound iron, as periplasmic reduction has been shown to be important for the uptake of siderophore-bound iron and 231 PepSY-like gene clusters encode a TonB receptor (Pfam accession PF03544) related to well-characterized outer membrane siderophore transporters ( Figure 4C ; Liu et al, 2018a ; Manck et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, C-starved cells have diminished rates of ammonium assimilation and potentially other N utilization pathways, even when cells are N limited (77). Notably, a recent study found that Alteromonas significantly reduced expression of genes involved in nitrogen metabolic pathways under carbon and iron colimitation (78).…”
Section: Discussionmentioning
confidence: 99%